Detection and Biological Characteristics of Alternaria alternata Resistant to Difenoconazole from Paris polyphylla var. chinensis, an Indigenous Medicinal Herb - Sun, Chunxia (Plant disease, 2021)
Black spot caused by Alternaria alternata (BSAA) is one of the most common diseases of Paris polyphylla var. chinensis, causing yield losses in China. Demethylation inhibitors (DMIs) have been used to control this disease in China for decades. Some farmers have complained about the decreased efficacy of DMIs against BSAA. The objective of this study was to detect and characterize the resistance of A. alternata against difenoconazole from P. polyphylla var. chinensis during 2018. Of the 22 isolates of A. alternata obtained from Sichuan Province in the southwest of China, 20 were resistant to difenoconazole. Mycelial growth rates and sporulation of the difenoconazole-resistant (DfnR) isolates were not different from those of the difenoconazole-sensitive (DfnS) isolates. No cross resistance between difenoconazole and tebuconazole or propiconazole was observed. Mutations were identified at gene AaCYP51 of DfnR isolates based on the sequence alignment of the DfnR and DfnS isolates. All of the mutations could be divided into three resistant genotypes, I (K715R + Y781C), II (K715R + D1140G + T1628A), and III (no mutation). The docking total score of the DfnS isolates was 5.6020, higher than the resistant genotype I (4.4599) or the resistant genotype II (3.8651), suggesting that the DMI resistance of A. alternata may be caused by the decreased affinity between AaCYP51 and difenoconazole